Multi-resonance thermal activation delayed fluorescence material based on long and short axis hybridization and application of multi-resonance thermal activation delayed fluorescence material in organic electroluminescent device

Through the design of long and short axis hybrid molecules, the RISC and fluorescence characteristics of MR-TADF materials are modulated, and the problems of rolling down efficiency and color purity deterioration at high brightness are solved, thereby achieving high efficiency and high color purity organic electricity Electroluminescent devices.

CN119176827AActive Publication Date: 2024-12-24JILIN UNIVERSITY

Patent Information

Application Number
CN202411298335.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2024-12-24
Estimated Expiration
2044-09-18

AI Technical Summary

Technical Problem

In existing MR-TADF materials, the RISC is slower, the triplet exciton annihilation and molecular aggregation-induced quenching effects are severe, resulting in serious roll-off of electroluminescent devices at high brightness.

Method used

Long-short-axis hybridization (HLSA) molecule design is adopted to enhance the RISC process through spin-orbit coupling of the short-axis framework. The long-axis framework ensures narrow band emission and high fluorescence quantum yield. Combined with the group design with different electron-giving capabilities, the excitation state is modulated. LR-CT and SR-CT characteristics.

Benefits of technology

Achieving high-efficiency electroluminescent devices maintain high efficiency at high brightness, overcoming the problems of efficiency attenuation and color purity deterioration at high brightness of MR-TADF materials, and obtaining organic electrochemical properties of high color purity and low efficiency roll-off Light emitting device.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119176827A_ABST
    Figure CN119176827A_ABST
Patent Text Reader

Abstract

The invention discloses a multi-resonance thermal activation delayed fluorescent material based on long and short axis hybridization and application of the multi-resonance thermal activation delayed fluorescent material in an organic light-emitting device, and belongs to the technical field of organic light-emitting devices. According to the invention, donors and cyano groups with different electron donating capacities are introduced into a multi-resonance framework, and the multi-resonance thermally activated delayed fluorescence material with MR-TADF molecule short-range charge transfer (SR-CT) properties and traditional TADF molecule long-range charge transfer (LR-CT) properties is designed and synthesized. The LR-CT property of the short-axis skeleton can enhance the spin-orbit coupling of the system and promote the multi-channel reverse intersystem crossing process from the triplet state to the singlet state without causing emission red shift and spectrum broadening; the SR-CT property of the long-axis skeleton ensures narrow half-peak width and high luminous efficiency, and ensures efficient luminescence under the conditions that the color fidelity is not influenced and the efficiency roll-off is reduced, and the prepared organic electroluminescent device realizes high efficiency, high color purity and low-efficiency roll-off.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of organic electroluminescent devices, and in particular relates to a multi-resonance thermally activated delayed fluorescence material based on long-short axis hybridization and an application thereof in organic electroluminescent devices. Background Art

[0002] Organic Light Emission Diodes (OLED) is a new type of display technology with the advantages of high brightness, fast response, wide viewing angle, simple process, and flexibility. It has made great progress in full-color display and lighting application technology and has become a hot trend in current industrialization. In recent years, the third-generation luminescent material-Thermal-Activated Delayed Fluorescence (TADF) material has been widely developed and applied in electronic devices because it can effectively utilize triplet excitons, and has become a frontier research hotspot in the field of luminescent materials. However, most of the current TADF materials adopt a donor-acceptor structure. The vibration coupling between the ground state and the excited state and the relaxation of the excited state structure cause the half-peak width (full-width at half maximum, FWHM>70nm) of its emission spectrum to be wide, which cannot meet the technical requirements of high color purity of full-color display technology. Although the device structure using filters or optical microcavities can meet the display requirements for color purity, this not only makes the device structure complex, but also causes a large energy loss, which is not conducive to energy saving and environmental protection requirements.

[0003] In recent years, new TADF materials with boron / nitrogen multiple resonance effect (MR) have been reported to achieve high color purity and high luminescence efficiency. Their unique short-range charge transfer (SRCT) electronic structure not only gives these materials a large oscillator strength (f) and the resulting high fluorescence quantum yield (PLQY), but also minimizes the bonding / antibonding characteristics, structural relaxation and vibration coupling of the excited state, thereby achieving narrow-band emission characteristics. However, compared with the donor-acceptor (DA) type TADF with long-range charge transfer (LRCT), typical MR characteristic materials exhibit a relatively slow reverse intersystem crossing (RISC) rate (k RISC For 10 3 -10 4 s-1 ), which usually leads to the accumulation of triplet excitons and subsequent exciton annihilation, resulting in severe efficiency roll-off at high brightness, hindering their commercial application potential. In addition, the boron / nitrogen multiple resonance system compound has a large rigid planar structure, strong interactions between molecules, and is easy to aggregate. When preparing electroluminescent devices, it is easy to produce aggregation-induced quenching effect, which further leads to the deterioration of the luminescent performance of the material and the color purity of the device.

[0004] Therefore, it is of great significance to develop new organic light-emitting materials with high efficiency, high color purity and the ability to maintain high efficiency at high brightness, which will play an important role in promoting the further popularization of OLEDs technology. Summary of the invention

[0005] The technical problem to be solved by the present invention is that k RISC The quenching effect of triplet exciton annihilation and aggregation-induced quenching between molecules is relatively slow, resulting in a serious efficiency roll-off of the electroluminescent device at high brightness. In view of the existing problems, the present invention provides a simple and effective strategy to improve the RISC of MR-TADF materials without affecting the color purity, that is, to modulate the LR-CT and SR-CT characteristics in the excited state through the "hybridized long-short axis (HLSA)" molecular design. The present invention is inspired by the long-short axis "thermal exciton" material, in which the LR-CT component of the short axis skeleton enhances the spin-orbit coupling (SOC) of the system, promotes the RISC process, and does not cause emission red shift and spectrum broadening, while the SR-CT component of the long axis skeleton ensures narrow-band emission and high PLQY. The electroluminescent device prepared by the present invention is conducive to achieving high efficiency at high brightness, overcoming the shortcomings of the serious attenuation of device efficiency and widening of the half-peak width of the MR-TADF material at high brightness.

[0006] The boron-containing multi-resonance thermally activated delayed fluorescence material based on long-short axis hybridization described in the present invention has a structural formula as shown below:

[0007]

[0008] Where R is:

[0009]

[0010] Furthermore, the multi-resonance thermally activated delayed fluorescence material based on long-short axis hybridization described in the present invention has a structural formula as shown in one of the following:

[0011]

[0012] The organic electroluminescent device prepared by the product of the present invention is composed of a cathode, an anode and one or more organic layers between the two electrodes, at least one of the organic layers is an organic light-emitting layer, and the organic light-emitting layer is composed of the multi-resonance thermally activated delayed fluorescent material based on long-short axis hybridization prepared by the present invention as a doped guest material and PhCzBCz as a doped host material, and the mass doping ratio of the guest material is 2-5%. The electroluminescent device can be used to prepare an organic electroluminescent display or an organic electroluminescent lighting source.

[0013] Furthermore, the present invention provides an organic electroluminescent device, which consists of a transparent substrate, an ITO conductive film (anode), a hole injection layer (HATCN), a hole transport layer (TAPC), an exciton blocking layer (TCTA and mCP), an organic light-emitting layer, an electron transport layer (TmPyPB), an electron injection layer (LiF) and a cathode layer (Al) from bottom to top, and all functional layers can be prepared by a vacuum evaporation film-forming process.

[0014] Preferably, the organic compounds used in the device are commercially available or prepared according to known literature or patents, and the molecular structure is shown below:

[0015]

[0016] The beneficial effects of the present invention are:

[0017] The multi-resonance thermally activated delayed fluorescence material based on long-short axis hybridization of the present invention has high luminescence efficiency, high reverse intersystem crossing rate and narrow half-width. In view of the existing problems, the present invention provides a simple and effective strategy to improve the RISC of MR-TADF materials without affecting the color purity. By introducing donors and cyano groups with different electron donating abilities into the MR-TADF framework, the designed and synthesized "HLSA" molecules have both the SR-CT properties of MR-TADF molecules and the characteristics of traditional DA molecules LR-CT. The LR-CT properties of the short-axis skeleton can enhance the SOC of the system and promote the multi-channel RISC process from triplet to singlet without causing emission red shift and spectral broadening; the SR-CT properties of the long-axis skeleton ensure narrow half-width and high PLQY, and ensure efficient luminescence without affecting color fidelity and reducing efficiency roll-off. The organic electroluminescent device prepared in this way overcomes the shortcomings of MR-TADF materials such as severe efficiency attenuation at high brightness, and realizes the preparation of organic electroluminescent devices with high efficiency, high color purity and low efficiency roll-off, which plays an important role in promoting the further popularization of organic electroluminescent technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1: Schematic diagram of the structure of the organic electroluminescent device prepared by the present invention, in which 1 is a transparent substrate, 2 is an ITO anode, 3 is a hole injection layer, 4 is a hole transport layer, 5 is an exciton blocking layer, 6 is an organic light-emitting layer, 7 is an electron transport layer, 8 is an electron injection layer, and 9 is a cathode.

[0019] Figure 2 :UV (Abs.), fluorescence (FL.) and low-temperature phosphorescence spectra (Phos.) of compound BN-1; the maximum absorption peak is 475nm, the main emission peak is at 496nm, which is blue-green light emission, and the half-peak width is 21nm; the energies of S1 and T1 are calculated to be 2.50eV and 2.32eV respectively through the main peak positions of fluorescence and low-temperature phosphorescence, and the ΔE of the two molecules can be calculated ST It is 0.18eV.

[0020] Figure 3 :UV, fluorescence and low-temperature phosphorescence spectra of compound BN-2; the maximum absorption peak is 474nm, the main emission peak is at 491nm, which is blue-green emission, and the half-peak width is 23nm; the energies of S1 and T1 are calculated to be 2.52eV and 2.32eV respectively through the main peak positions of fluorescence and low-temperature phosphorescence, and the ΔE of the two molecules can be calculated ST is 0.20eV.

[0021] Figure 4 :UV, fluorescence and low-temperature phosphorescence spectra of compound BN-3; the maximum absorption peak is 475nm, the main emission peak is at 495nm, which is blue-green emission, and the half-peak width is 26nm; the energies of S1 and T1 are calculated to be 2.50eV and 2.32eV respectively through the main peak positions of fluorescence and low-temperature phosphorescence, and the ΔE of the two molecules can be calculated ST It is 0.18eV.

[0022] Figure 5 : The external quantum efficiency curve of the electroluminescent device prepared by compound BN-1, the maximum external quantum efficiency is 35.7%, at a brightness of 100 cd m -2 When , the external quantum efficiency is 32.1%; the inset is the electroluminescence spectrum under a driving voltage of 6V. The main peak of electroluminescence is located at 504nm, which is green light emission, and has very high color purity, with a half-peak width of 31nm.

[0023] Figure 6 : The external quantum efficiency curve of the electroluminescent device prepared by compound BN-2, the maximum external quantum efficiency is 37.9%, at a brightness of 100 cd m -2 When , the external quantum efficiency is 34.8%; the inset is the electroluminescence spectrum under a driving voltage of 6V. The main peak of the electroluminescence is located at 504nm, which is the emission of green light, and it has very high color purity, with a half-peak width of 31nm.

[0024] Figure 7 : The external quantum efficiency curve of the electroluminescent device prepared by compound BN-3, the maximum external quantum efficiency is 33.7%, at a brightness of 100 cd m -2 When , the external quantum efficiency is 25.2%; the inset is the electroluminescence spectrum under a driving voltage of 6V. The main peak of electroluminescence is located at 504nm, which is green light emission, and has very high color purity, with a half-peak width of 35nm. DETAILED DESCRIPTION

[0025] The present invention is further described below in conjunction with the accompanying drawings to facilitate understanding of the present invention by those skilled in the art. Obviously, the described embodiments are only a part of the experiment, not all embodiments, and non-essential modifications, equivalent substitutions and improvements made to the present invention by those skilled in the art according to the above invention content should all be included in the protection scope of the present invention. The raw materials mentioned below are all commercially available or prepared according to known documents or patents, and the process steps and preparation methods not mentioned are all process steps and preparation methods well known to those skilled in the art.

[0026] Example 1: The preparation of BN-1 in this example is as follows:

[0027]

[0028] Synthesis of M1: Under nitrogen protection, 60 mL of anhydrous DMF (N, N-dimethylformamide) solution containing 3,6-di-tert-butylcarbazole (9.8 g, 35.2 mmol) was slowly added dropwise to a mixture of cesium carbonate (13.0 g, 40.0 mmol) and 50 mL of anhydrous DMF within 20 minutes. After the reaction system was stirred at room temperature for 2 hours, 20 mL of anhydrous DMF solution containing 1-bromo-2,6-difluorobenzene (3.1 g, 16.0 mmol) was injected dropwise therein within 15 minutes, and the mixture was heated to 140 ° C and stirred for 24 hours, and then cooled to room temperature. The reaction system was poured into ice water (2000 g), the white solid was filtered out and dried in a vacuum oven, and then further purified by column chromatography using a mixed eluent of dichloromethane / petroleum ether (volume ratio 1:3) to obtain a white solid M1 (9.1 g) with a yield of 80%. 1 H NMR (500MHz, CDCl3) δ (ppm): 8.16 (d, J = 1.9 Hz, 4H), 7.67 (dd, J = 8.8, 6.6 Hz, 1H), 7.6 1(d,J=8.4Hz,2H),7.51(dd,J=8.6,1.9Hz,4H),7.12(d,J=8.6Hz,4H),1.47(s,36H). 13C NMR (151 MHz, CDCl3) δ (ppm): 143.03, 139.66, 139.27, 130.86, 129.30, 125.83, 123.81, 123.38, 116.47, 109.40, 34.81, 32.07; Mass spectrum MALDI-TOF (m / z) [M + ]: The measured value is 711.5 and the theoretical value is 711.8.

[0029]

[0030] Synthesis of M2: Under nitrogen protection and ice-water bath, a pentane solution of tert-butyl lithium (1.3M, 19.4 mL, 25.2 mmol) was slowly added dropwise to a solution of M1 (9.0 g, 12.6 mmol) in tert-butylbenzene (100 mL), then heated to 60 ° C and stirred for 2 hours, and then boron tribromide (2.4 mL, 25.2 mmol) was added at -30 ° C, and the reaction system was stirred at room temperature for 1 hour. Finally, N, N-diisopropylethylamine (3.5 mL, 25.2 mmol) was added at 0 ° C, and the reaction system was stirred at 130 ° C for 6 hours and then cooled to room temperature. 5 mL of methanol was added to the reaction system to quench the residual boron tribromide. The mixture was extracted with 200 mL of water and 200 mL of dichloromethane, the organic layers were combined, concentrated in vacuo, and then further purified by column chromatography using a mixed eluent of dichloromethane / petroleum ether (volume ratio 1:20) to give a yellow solid M2 (2.1 g) with a yield of 26%. 1 H NMR (500MHz, CDCl3) δ (ppm): 9.12 (d, J = 1.8 Hz, 2H), 8.46 (d, J = 1.7 Hz, 2H), 8.38 (d, J = 8.8 Hz, 2H), 8.3 3–8.24(m,4H),7.99(td,J=8.3,1.3Hz,1H),7.65(dd,J=8.7,2.1Hz,2H),1.67(s,18H),1.53(s,18H). 13 C NMR (151 MHz, CDCl3) δ (ppm): 145.24, 144.58, 144.25, 141.54, 138.36, 132.99, 129.79, 127.05, 124.32, 123.65, 123.19, 121.56, 120.62, 117.22, 114.12, 107.93, 35.18, 34.81, 32.21, 31.88; Mass spectrum MALDI-TOF (m / z) [M + ]: The measured value is 640.5 and the theoretical value is 640.7.

[0031]

[0032] Synthesis of M3: Under nitrogen protection, the catalyst methoxy(cyclooctadiene)iridium(I) dimer (43.1 mg, 0.065 mmol) and 4,4'-di-tert-butyl-2,2'-bipyridine (34.9 mg, 0.13 mmol) were added to a solution of M2 (4.20 g, 6.5 mmol) and biboric acid pinacol ester (1.68 g, 6.6 mmol) in ultra-dry tetrahydrofuran (60 mL). The mixture was then bubbled with nitrogen for 5 minutes, heated to reflux and stirred for 24 hours. After cooling to room temperature, the reaction mixture was directly concentrated under reduced pressure, and then further purified by column chromatography using a mixed eluent of dichloromethane / petroleum ether (volume ratio 1:20) to obtain a yellow solid M3 (4.50 g) with a yield of 90%. 1 H NMR (500MHz, CDCl3) δ (ppm): 9.14 (d, J = 1.9 Hz, 2H), 8.79 (s, 2H), 8.53 (d, J = 8.8 Hz, 2H), 8.48 (d, J = 1.8 Hz,2H),8.27(d,J=2.0Hz,2H),7.74(dd,J=8.8,2.1Hz,2H),1.67(s,18H),1.54(s,18H),1.49(s,12H). 13 C NMR (151 MHz, CDCl3) δ (ppm): 145.17, 144.55, 143.68, 141.64, 138.48, 129.77, 126.93, 124.59, 123.75, 121.65, 120.75, 117.10, 114.44, 113.77, 84.34, 35.18, 34.82, 32.21, 31.87, 25.09; Mass spectrum MALDI-TOF (m / z) [M + ]: The measured value is 766.8 and the theoretical value is 766.7.

[0033]

[0034] Synthesis of M4: Under nitrogen protection, carbazole (1.67 g, 10.0 mmol), 3,5-dibromobenzonitrile (3.13 g, 12.0 mmol), tris(dibenzylideneacetone)dipalladium (277 mg, 0.30 mmol), tri-tert-butylphosphine tetrafluoroborate (147 mg, 0.50 mmol), sodium tert-butoxide (1.92 g, 20 mmol) were dissolved in 100 mL toluene solution, and refluxed at 110°C for 24 hours under nitrogen protection. The liquid was extracted with dichloromethane, concentrated to obtain a crude product, and separated and purified by column chromatography, with the developing solvent being petroleum ether: dichloromethane (volume ratio 10:1), to obtain a white solid M4 (2.45 g, yield: 71%). 1H NMR (500 MHz, DMSO) δ (ppm): 8.36–8.32 (m, 1H), 8.30–8.25 (m, 4H), 7.48 (d, J = 3.6 Hz, 4H), 7.38–7.32 (m, 2H); Mass spectrum MALDI-TOF (m / z) [M + ]: The measured value is 347.1 and the theoretical value is 347.2.

[0035]

[0036] Synthesis of BN-1: Under nitrogen protection, M4 (347 mg, 1 mmol), M3 (766 mg, 1 mmol), K2CO3 (2.76 g, 20 mmol), Pd (PPh3) 4 (23 mg, 0.02 mmol) were mixed and added to a 100 mL flask, and then 20 mL toluene and 10 mL water were added, heated to 90 ° C and stirred for 12 hours. After cooling to room temperature, the reaction mixture was poured into water (100 mL), extracted with dichloromethane and water, and the combined organic layer was condensed in vacuo, and purified by column chromatography with a mixed eluent of dichloromethane / petroleum ether (volume ratio 1: 1) to obtain a light yellow solid BN-1 (550 mg) with a yield of 61%. 1 H NMR (500MHz, CDCl3) δ (ppm): 9.13 (s, 2H), 8.51 (d, J = 13.6Hz, 4H), 8.43 (s, 1H), 8.39 (d, J = 8.8Hz, 2H), 8.30 (d, J = 1.7Hz, 2H), 8.27–8.21(m,3H),8.08(s,1H),7.74–7.66(m,4H),7.58(t,J=7.3Hz,2H),7.44(t,J=7.4Hz,2H),1.69(s,18H),1.56(s,18H). 13 C NMR (126 MHz, CDCl3) δ (ppm): 145.61, 144.80, 141.87, 141.60, 140.12, 139.46, 138.05, 130.12, 129.68, 129.17, 128.89, 127.20, 126.56, 124.78, 124.05, 123.70, 121.56, 121.02, 120.79, 118.19, 117.45, 114.86, 114.14, 109.41, 106.25, 35.17, 34.84, 32.14, 31.81; Mass Spectrometry MALDI-TOF (m / z) [M + ]: The measured value is 907.1 and the theoretical value is 907.0.

[0037] Example 2: The preparation of BN-2 in this example is as follows:

[0038]

[0039] Synthesis of M5: Under nitrogen protection, diphenylamine (1.69 g, 10.0 mmol), 3,5-dibromobenzonitrile (3.13 g, 12.0 mmol), tris(dibenzylideneacetone)dipalladium (277 mg, 0.30 mmol), tri-tert-butylphosphine tetrafluoroborate (147 mg, 0.50 mmol), sodium tert-butoxide (1.92 g, 20 mmol) were dissolved in 100 mL toluene solution, and refluxed at 110°C for 24 hours under nitrogen protection. The liquid was extracted with dichloromethane, concentrated to obtain a crude product, and separated and purified by column chromatography, with the developing solvent being petroleum ether: dichloromethane (volume ratio 10:1), to obtain a white solid M5 (2.85 g, yield: 82%). 1 H NMR (500 MHz, DMSO) δ (ppm): 7.60 (s, 1H), 7.42 (t, J = 7.7 Hz, 4H), 7.19 (dd, J = 31.4, 13.9 Hz, 8H); Mass spectrum MALDI-TOF (m / z) [M + ]: The measured value is 349.4 and the theoretical value is 349.2.

[0040]

[0041] Synthesis of BN-2: Under nitrogen protection, M5 (349 mg, 1 mmol), M3 (766 mg, 1 mmol), K2CO3 (2.76 g, 20 mmol), Pd (PPh3) 4 (23 mg, 0.02 mmol) were mixed and added to a 100 mL flask, and then 20 mL toluene and 10 mL water were added, heated to 90 ° C and stirred for 12 hours. After cooling to room temperature, the reaction mixture was poured into water (100 mL), extracted with dichloromethane and water, and the combined organic layer was condensed in vacuo, and purified by column chromatography with a mixed eluent of dichloromethane / petroleum ether (volume ratio 1: 1) to obtain a light yellow solid BN-2 (580 mg) with a yield of 64%. 1 H NMR (500MHz, CD2Cl2) δ (ppm): 9.05 (s, 2H), 8.52 (s, 2H), 8.30 (d, J = 1.6Hz, 2H), 8.13 (s, 2H), 8.02 (d, J = 8.7Hz, 2H), 7. 72(s,1H),7.63(dd,J=8.7,1.6Hz,2H),7.45(dd,J=18.9,11.0Hz,5H),7.34–7.20(m,7H),1.71(s,18H),1.61(s,18H). 13C NMR (126 MHz, CDCl3) δ (ppm): 149.14, 146.58, 145.27, 144.62, 142.89, 142.59, 141.59, 138.06, 129.76, 127.12, 125.39, 124.62, 123.77, 123.09, 122.57, 121.57, 120.87, 119.08, 117.32, 113.91, 105.97, 35.20, 34.85, 32.21, 31.89; Mass Spectrometry MALDI-TOF (m / z) [M + ]: The measured value is 909.2 and the theoretical value is 909.0.

[0042] Example 3: The preparation of BN-3 in this example is as follows:

[0043]

[0044] Synthesis of M6: Under nitrogen protection, diphenylamine (1.99 g, 10.0 mmol), 3,5-dibromobenzonitrile (3.13 g, 12.0 mmol), tris(dibenzylideneacetone)dipalladium (277 mg, 0.30 mmol), tri-tert-butylphosphine tetrafluoroborate (147 mg, 0.50 mmol), sodium tert-butoxide (1.92 g, 20 mmol) were dissolved in 100 mL toluene solution, and refluxed at 110°C for 24 hours under nitrogen protection. The liquid was extracted with dichloromethane, concentrated to obtain a crude product, and separated and purified by column chromatography, with the developing solvent being petroleum ether: dichloromethane (volume ratio 10:1), to obtain a white solid M6 (2.65 g, yield: 70%). 1 H NMR (500MHz, DMSO) δ (ppm): 8.03 (s, 1H), 7.69 (d, J = 10.0Hz, 2H), 7.37 (d, J = 7.6Hz, 2H), 7 .24(t,J=7.6Hz,2H),7.14(t,J=7.5Hz,2H),6.88(d,J=8.1Hz,2H); Mass spectrum MALDI-TOF(m / z)[M + ]: The measured value is 379.4 and the theoretical value is 379.3.

[0045]

[0046] Synthesis of BN-3: Under nitrogen protection, M6 (379 mg, 1 mmol), M3 (766 mg, 1 mmol), K2CO3 (2.76 g, 20 mmol), Pd (PPh3) 4 (23 mg, 0.02 mmol) were mixed and added to a 100 mL flask, and then 20 mL toluene and 10 mL water were added, heated to 90 ° C and stirred for 12 hours. After cooling to room temperature, the reaction mixture was poured into water (100 mL), extracted with dichloromethane and water, and the combined organic layer was condensed in vacuo, and purified by column chromatography with a mixed eluent of dichloromethane / petroleum ether (volume ratio 1: 1) to obtain a light yellow solid BN-3 (530 mg) with a yield of 56%. 1 H NMR(500MHz, CD2Cl2)δ(ppm):9.03(s,1H),8.54(t,J=5.8Hz,1H),8.40–8.17(m,7H),7.93(d,J=9.3Hz,1H),7.81(s,1H),7.76–7.5 8(m,4H),7.55(s,1H),7.53–7.46(m,2H),7.39(dd,J=12.0,5.9Hz,2H),7.25(dt,J=21.5,6.2Hz,3H),1.68(s,18H),1.58(s,18H). 13 C NMR (126 MHz, CDCl3) δ (ppm): 145.91, 145.48, 144.79, 142.01, 141.60, 138.08, 130.20, 129.70, 129.03, 128.58, 127.50, 127.19, 125.61, 124.63, 124.13, 123.60 (s), 123.10, 121.56, 120.96, 118.79, 117.41, 114.48, 114.04, 109.52, 106.22, 35.16, 34.85, 32.00, 22.55; Mass Spectrometry MALDI-TOF (m / z) [M + ]: The measured value is 939.4 and the theoretical value is 939.1.

[0047] The technical effects and advantages of the present invention are demonstrated and verified by applying the compound of the present invention to an organic electroluminescent device to test the actual performance.

[0048] Effect Example 1: Preparation of organic electroluminescent device BN-1

[0049] The technical effects and advantages of the present invention are demonstrated and verified by applying the compounds of the present invention to organic electroluminescent devices to test their actual performance. The specific device preparation process and device performance test experimental operation are as follows: The device preparation process is as follows: Preparation of indium tin oxide (ITO) conductive glass substrate: The substrate is cleaned in ultrasonic bath with deionized water, isopropanol, acetone, toluene, acetone, and isopropanol for 20 minutes each, and dried in an oven; After treating the surface of the ITO conductive glass substrate in an ultraviolet ozone cleaning machine for 40 minutes, it is moved into a vacuum evaporation device (the pressure in the chamber is less than 2×10 -4 Pa); on the anode ITO conductive glass, a hole injection layer HATCN is vacuum-deposited with a thickness of 6 nm; on HATCN, a hole transport layer TAPC is vacuum-deposited with a thickness of 30 nm: on TAPC, an exciton blocking layer TCTA is evaporated with a thickness of 5 nm; on TCTA, an exciton blocking layer mCP is evaporated with a thickness of 5 nm; on mCP, an organic light-emitting layer EML is evaporated with a thickness of 20 nm; on the organic light-emitting layer, an electron transport layer TmPyPB is evaporated with a thickness of 40 nm; on TmPyPB, an electron injection layer LiF is evaporated with a thickness of 1 nm; on LiF, a cathode Al is evaporated with a thickness of 100 nm.

[0050] The structure of the organic electroluminescent device BN-1 is as follows: ITO / HATCN (6nm) / TAPC (30nm) / TCTA (5nm) / mCP (5nm) / EML (20nm) / TmPyPB (40nm) / LiF (1nm) / Al (100nm), where EML represents the light-emitting layer, and the light-emitting layer is composed of a main material PhCzBCz with a mass percentage of 97% and a guest light-emitting material BN-1 with a mass percentage of 3%.

[0051] A direct current voltage was applied to the organic electroluminescent device BN-1 prepared in this example, and the luminescence performance was evaluated using a Spectrascan PR655 luminance meter, and the current-voltage characteristics were measured using a computer-controlled Keithley 2400 digital source meter. As luminescence characteristics, the electroluminescent spectrum, half-peak width, CIE color coordinates, external quantum efficiency (%), power efficiency (lm / W), maximum brightness (cd / m 2 The detailed electroluminescent performance data of the device are listed in Table 1. The measured values ​​of the device are as follows: the spectral peak is 504nm, the half-peak width is 31nm, the CIE color coordinates are (0.13, 0.62), the maximum power efficiency is 91.1lm / W and the maximum brightness is 37258cd / m 2 , the maximum external quantum efficiency is 35.7%. When the brightness reaches 100cd / m 2 and 1000cd / m2 When , the external quantum efficiency can still be maintained at 32.1% and 18.5%.

[0052] Effect Example 2: Preparation of organic electroluminescent device BN-2

[0053] The preparation method is the same as that of Example 1, except that the guest luminescent material BN-1 used in the luminescent layer is replaced by BN-2. The specific device structure is as follows: ITO / HATCN (6nm) / TAPC (30nm) / TCTA (5nm) / mCP (5nm) / EML (20nm) / TmPyPB (40nm) / LiF (1nm) / Al (100nm), EML represents the luminescent layer, and the luminescent layer is composed of 97% by weight of the main material PhCzBCz and 3% by weight of the guest luminescent material BN-2.

[0054] A direct current voltage was applied to the organic electroluminescent device BN-2 prepared in this example, and the luminescence performance was evaluated using a Spectrascan PR655 brightness meter, and the current-voltage characteristics were measured using a computer-controlled Keithley 2400 digital source meter. As luminescence characteristics, the electroluminescent spectrum, half-peak width, CIE color coordinates, external quantum efficiency (%), power efficiency (lm / W), maximum brightness (cd / m 2 The detailed electroluminescent performance data of the device are listed in Table 1. The measured values ​​of the device are as follows: the spectral peak is 504nm, the half-peak width is 31nm, the CIE color coordinates are (0.18, 0.62), the maximum power efficiency is 94.7lm / W and the maximum brightness is 32132cd / m 2 , the maximum external quantum efficiency is 37.9%. When the brightness reaches 100cd / m 2 and 1000cd / m 2 When , the external quantum efficiency can still be maintained at 34.8% and 21.8%.

[0055] Effect Example 3: Preparation of organic electroluminescent device BN-3

[0056] The preparation method is the same as that of Example 1, except that the guest luminescent material BN-1 used in the luminescent layer is replaced by BN-3. The specific device structure is as follows: ITO / HATCN (6nm) / TAPC (30nm) / TCTA (5nm) / mCP (5nm) / EML (20nm) / TmPyPB (40nm) / LiF (1nm) / Al (100nm), EML represents the luminescent layer, and the luminescent layer is composed of 97% by weight of the main material PhCzBCz and 3% by weight of the guest luminescent material BN-3.

[0057] A direct current voltage was applied to the organic electroluminescent device BN-3 prepared in this example, and the luminescence performance was evaluated using a Spectrascan PR655 luminance meter, and the current-voltage characteristics were measured using a computer-controlled Keithley 2400 digital source meter. As luminescence characteristics, the electroluminescent spectrum, half-peak width, CIE color coordinates, external quantum efficiency (%), power efficiency (lm / W), maximum brightness (cd / m 2 The detailed electroluminescent performance data of the device are listed in Table 1. The measured values ​​of the manufactured device are spectral peak of 504nm, half-peak width of 35nm, CIE color coordinates of (0.13, 0.61), maximum power efficiency of 99.4lm / W and maximum brightness of 17515cd / m 2 , the maximum external quantum efficiency is 33.7%. When the brightness reaches 100cd / m 2 and 1000cd / m 2 When , the external quantum efficiency can still be maintained at 25.2% and 12.7%.

[0058] Table 1: Data parameters of electroluminescent device provided by the effect embodiment

[0059]

[0060] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A multi-resonance thermally activated delayed fluorescence material based on long-short axis hybridization, the structural formula of which is as follows: Where R is 2. The multi-resonance thermally activated delayed fluorescent material based on long-short axis hybridization according to claim 1, wherein the structural formula is as shown in one of the following:

3. Use of the multi-resonance thermally activated delayed fluorescence material based on long-short axis hybridization according to claim 1 or 2 in the preparation of an organic electroluminescent device.

4. The use of a multi-resonance thermally activated delayed fluorescence material based on long-short axis hybridization in the preparation of an organic electroluminescent device as claimed in claim 3, characterized in that: The organic electroluminescent device is composed of a cathode, an anode and one or more organic layers between the two electrodes, at least one of the organic layers is an organic light-emitting layer, and the organic light-emitting layer is composed of a multi-resonance thermally activated delayed fluorescent material based on long-short axis hybridization as described in claim 1 or 2 as a doped guest material and PhCzBCz as a doped host material, and the mass doping ratio of the guest material is 2-5%.

5. The use of a multi-resonance thermally activated delayed fluorescence material based on long-short axis hybridization in the preparation of an organic electroluminescent device as claimed in claim 4, characterized in that: The organic electroluminescent device consists of a transparent substrate, an ITO conductive film anode, a hole injection layer, a hole transport layer, an exciton blocking layer, an organic light-emitting layer, an electron transport layer, an electron injection layer and a cathode layer from bottom to top.

6. Use of a multi-resonance thermally activated delayed fluorescence material based on long-short axis hybridization in the preparation of an organic electroluminescent device as claimed in claim 4 or 5, characterized in that: The electroluminescent device is used for preparing an organic electroluminescent display or an organic electroluminescent lighting source.

Citation Information

Patent Citations

  • Green-light narrow-spectrum three-coordinate boron light-emitting compound containing carbazole skeleton, preparation method and application thereof

    CN113336782A

  • Multi-resonance type thermally activated delayed fluorescence material with spatial three-dimensional structure, electronic device and application of multi-resonance type thermally activated delayed fluorescence material

    CN113651841A

  • Narrow-emission efficient multi-resonance light-emitting material, preparation method thereof and organic light-emitting diode

    CN114014881A

  • Organic compound based on steric hindrance type BN and application thereof

    CN117964649A

Cited By

  • Multi-resonance organic dye as well as preparation method and application thereof

    CN120081861A